The foreign career path attraction factors of Lithuanian talent labour - Aukštuolytė, Justina (2019)
The main goal of this paper is to analyse the trends of Talent Acquisition as a marketing strategy and implement the results to create a Foreign Talent Acquisition Strategy for a boutique recruitment agency in Lithuanian market. The literature regarding the topic was analysed in order to guide the research. A qualitative research was conducted in order to receive up to date, primary data about employees’ job search preferences and attraction factors to complement the theoretical frameworks. The results gained from the empirical research were used as a guideline for the development of a Foreign Talent Acquisition strategy.